Adaptasi Kebijakan Pembangunan Berkelanjutan Terhadap Risiko Banjir Rob Di Wilayah Pesisir Belawan - Sigalingging, Anggitha Serevina; Manalu, Dimpos; Tobing, Artha Lumban (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study examines the adaptation of sustainable development policies to mitigate the risk of tidal flooding in the coastal area of Belawan, specifically in Belawan Bahagia Village, Medan Belawan District. The researchaims to analyze the effectiveness of current policies in addressing tidal flood risks and identify the challenges faced in their implementation. Using a qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that while the community is highly aware of the risks posed by tidal flooding, the existing policies, such as the construction of embankments and drainage systems, are not fully effective due to limited resources and insufficient community involvement. The study concludes that enhancing community participation, improving infrastructure, and fostering collaboration between the government, private sector, and local communities are crucial for developing more effective and sustainable adaptation strategies.